Comparative life cycle assessment of perennial and annual crop production : impact of farming systems and management practices - David, Christophe; Amaro, Xabier; Rosentrater, Kurt A.; Ghnimi, Sami (Frontiers in Sustainable Food Systems, 2025)
The Intermediate Wheatgrass (IWG) Thinopyrum intermedium (Host) Barkworth & D.R. Dewey, marketed under the trade name Kernza® has been tested in France with a group of farmers since 2017. The Life Cycle Assessment (LCA) is a recognized methodology to assess the potential environmental impacts and resources consumption associated with a production system. An attributional LCA following ISO 14040/44 was conducted, focusing on static comparisons. The main purpose of this paper was to estimate the “cradle-to-farm gate” environmental effects caused by the cultivation of intermediate wheatgrassin comparison with the main crops produced, among which soft wheat and maize grain stand out. This research has been achieved with 6 farmers, 3 under organic and 3 under conventional production. A comparative assessment was carried out per year and under 3 years of crop rotation to determine contributions to the environmental impact. Several impact categories were evaluated, including global warming potential (GWP), ozone depletion (OD), freshwater eutrophication (FE) freshwater ecotoxicity (FEC) and acidification (AC). Intermediate wheatgrass (IWG) shows significantly better environmental performance per hectare than annual crops due to its perennial nature with limited soil preparation and lower input requirements. Conversely, IWG performs worse per ton due to its relatively low grain yield. IWG results shows higher contribution of mechanical practices than cash crops with 70% for GWP and OD and 20% with FE, AC and FEC due to low use of fertilizers and pesticides over the 3yr. Grain yields of organically grown crops are lower than those of conventionally grown crops, regardless of the crop. Conventional management shows higher environmental impacts than organic per hectare on IWG but also on annual crops in each category. Conversely organic management on IWG conduct to higher GWP and FE per volume due to regular mechanic weeding, inducing fuel consumption, and organic manure applied before sowing. The results on IWG show significant difference on environmental performance per hectare and per ton between establishment year inducing soil preparation, sowing and fertilization and succeeding years with limited practices except weed management and/or mulching.
Publisher Copyright: Copyright © 2025 David, Amaro, Rosentrater and Ghnimi.
Keywords: conventional; farming systems; intermediate wheatgrass; Kernza; life cycle assessment; on-farm; organic